Status and challenges of e-waste management in Malaysia - Songip, Ahmad Rahman (2015)
As the economy grows, more Malaysians can afford to purchase new electronic and electrical equipments and discarded the old ones. The ever-increasing and rapidly growing volume of electrical and electronic waste (e-waste) in Malaysia will become a serious threat to the environment, if the situation is not manage properly. E-waste is now considered as a new and emerging type of hazardous waste and currently regarded as the most challenging waste stream in Malaysia. A comprehensive research on holistic approach to e-waste management is therefore imperative to protect the environment in the future. In view of this situation, this study explores e-waste's past and present status to effectively manage the challenges for the future. The focus will be on household generated e-waste as currently there is no specific law to control this type of ewaste in Malaysia. In details, through the use of qualitative research method, this study will look at the status, current practises and legislation related to the management of household generated e-waste, for a sustainable environmental management in Malaysia.